Surrealism in the Hieronymus Bush Paintings - Hamid Ali, Israa; Salman Kazem, Bushra (Dirasat: Human and Social Sciences, 2022)
The first chapter of this research deals with the problem that the reseach addresses , its importance, and the need for it. The chapter also included the purpose of the research (the discovery of the mechanism of the work of Surrealism in the drawings of Hieronymus Bosch), within the period (1480-1516). In the relevant sources, the researchers concluded the first chapter by specifying the terms in the title of the research. The second chapter includes the theoretical framework and the previous studies. The theoretical framework consists of two sections dealing with the first topic: The Conceptual Dimensions of Surrealism, as well as the Total Concepts on which Surrealism was based. While the third chapter included research procedures, including the research community of (49), the nature of the selection of the research sample (4) plates, the procedures that were taken in the preparation of the research tool as well as the analysis of the research sample. The fourth chapter included the results of the research, conclusions, recommendations and proposals, and the results of the research: 1- Surrealism in Bush (Bush) achieved a large percentage after revealed many approaches in style and indications and content. 2- Approaches (Bush) in his Surrealist approach of the style (Salvador Dali). Both of them employ real things, simulated or after the change in structure as the composition and variance, as well as the approach to the quality of the subject. 3- The imagination has an import ant role and space in the art of (Bush) because he was able to present subjects in unfamiliar scenes in tangible reality